Culturally Sensitive Teaching in Finland's Basic Education: A Comparative Study of the 'Diversity Pedagogy' Model - Garcia Lagarda, Dacil Aline (My University, 2009)
The purpose of this thesis is to compare the practice of teachers in the Finnish classroom with a model of culturally sensitive teaching. By this comparison, the research examines the influence of culture in the teaching-learning process: how the cultural background of every student and every instructor cannot be detached from this everyday process. Several researchers have studied the power of culture in education, and today the rising of a multicultural classroom is inevitable. According to a culturally sensitive teaching, the role of the educator is to be aware and try to identify cultural situations, and to create an equal environment of learning for every student. The need for a special teaching approach regarding culturally diverse students is the argument for this research. The performance of these students is conditioned by the equal accessibility they have to instruction. The focus of this research was Basic Education, and teachers working with immigrant students were approached. The method of analysis was based on the ‘Diversity Pedagogy’ model, proposed by educator Rosa Hernández Sheets. This model helped to approach different dimensions of instruction in the classroom, since it covered important areas in the development of the students. The study aims to state the concepts of multicultural teaching and the adversities that minority students experience. The findings and conclusions were supportive of the need of specialized attention for those students who differ from the mainstream culture. Finnish education considers the presence of culturally diverse students in their classrooms and offers special education. However, this type of special instruction was perceived specifically in the classrooms teaching only immigrant children and it faded in the regular classes when those immigrant children were integrated with the Finnish pupils.
Keywords: Diversity; Basic Education; Teaching-Learning; Culture; Immigrants; fi=Englannin kieli|en=English language|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|